Features of the formation of the American philosophical novel: the influence of transcendentalism, pragmatism, postmodernism, individualism, utopian and dystopian tradition - Yevstegniyeva, Emine Sergeyevna (The Lingua Spectrum, 2026)
This article examines how three key American philosophical movements – transcendentalism, pragmatism, individualism, and postmodernism – influenced the emergence and development of the American philosophical novel as an independent literary genre. It analyzes how transcendentalism enriched novels with psychologism and symbolism, pragmatism shifted the emphasis to practical experience and the consequences of actions, and individualism made the individual and their internal conflicts central. The paper identifies common features of such works and traces how these ideas interacted within American culture, concluding that their synthesis formed a unique tradition of the philosophical novel in the United States. These trends contributed to the development of a complex artistic form in which philosophical ideas are organically intertwined with literary experimentation. The article provides analysis of the works of famous American artists such as “Nature” (1836) by Ralph Waldo Emerson, “Herzog” (1964) by Saul Below, “Gravity’s Rainbow” by Thomas Pynchon (1973), “Atlas Shrugged” (1957), “The Fountainhead” (1943) by Ayn Rand, “Breakfast of Champions or Goodbye Black Monday!” (1973) by Kurt Vonnegut.